EVALUATION OF THE MORAL-PSYCHOLOGICAL STATUS OF THE MILITARY SERVICE OF THE NATIONAL GUARDS OF UKRAINE: THE THEORETICAL ASPECT - Prykhodko І. І.; Voloshko S. А.; Hunbin К. Yu. (Honor and Law, 2019)
Service-combat activities of military men of the National Guard of Ukraine is connected with the fulfillment of tasks of increased danger and complexity, it occurs mainly in complex, extreme and emergency situations. However, due to the influence of professional stress, physical and mental stress, chronic fatigue, irregular working hours, servicemen often are in a low moral and psychological state, reduces or excludes the effectiveness of the solution of their combat tasks. A stable positive moral and psychological state of servicemen is the key to the success of the performance of combat-combat activities. Therefore, the purpose of the article is to analyze the existing methods for assessing the moral and psychological state of servicemen of the security forces and defense of Ukraine in various conditions of performing service (combat) tasks.The analysis showed that at the present stage of reforming the armed formations of Ukraine, both the Armed Forces and the National Guard of Ukraine, a number of differences in the understanding of certain provisions of this theoretical framework and the real relation to the phenomenon of the “moral and psychological state” are revealed. The choice of methods for predicting the moral and psychological state must be differentiated depending on the nature, content, volume, purpose, tasks and depth, interval, and forecasting period. Similar conditions for the implementation of the service-combat activities are characterized by a negative impact on the human psyche of a wide range of adverse, discomfortable and threatening factors that form a high level of professional stress. Consequently, the servicemen the National Guard of Ukraine performing service-combat activities are exposed not only to the physical threat (personal health, life), but also to the significant risk of stress, neuropsychiatric disorders and mental disadaptation. The latter are often the direct cause of disruptions in professional activity, loss or significant decline in performance, interpersonal conflicts, violations of discipline, alcohol abuse and other negative phenomen. Thus, a stable positive moral and psychological state of servicemen is a guarantee of the success of service-combat activities implementation. Consequently, the assessment of the moral and psychological state of the personnel of the National Guard of Ukraine during the performance of the service-combat activities in complicated or extreme conditions is relevant.